The Impact of Fintech and Economic Development on Carbon Emissions in Mobile Money Economies - Thangaiyarkarasi, N.; Vanitha, S. (International Journal of Energy Economics and Policy, 2025)
Innovation is essential for accomplishing green and low-carbon objectives, which drives industrial upgrading and transformation. In order to improve the financial services industry's capacity for innovation, numerous countries actively encourage the growth of FinTech. This will surely contribute to the development of industry and technology in the field of a low-carbon, green economy. This research examined the nexus between carbon emissions (CO2) and fintech in the mobile money economies. Using the variables of fintech, carbon emissions, domestic credit to the private sector, foreign direct investment, GDP, and trade, the study employed statistical tools for the Generalized Linear Model (GLM) and unit root test, over a period of ten years, from 2013 to 2022. The study's findings confirmed that fintech did have a positive effect on carbon emissions and will aid financial institutions in developing a green economy and encourage the low-carbon economy to meet the objectives of the Paris Agreement. The study concluded that Fintech (Financial Technology) is the best financial strategy for reducing Carbon emissions (CO2) at the global level.